A edição da edição e o efeito de controle de sentidos: análise do funcionamento e da posição-sujeito-repórter no programa Profissão Repórter - Madeira, Alex Lourenço (2020)
This research, based on the French Discourse Analysis, aims to analyze the working and role of the subject-reporter in Profissão Reporter TV show. The image one has of the reporter is of someone who produces reports and updates viewers with everyday facts, in a photographic effect of reality, as if only he could communicate and the senses were transparent. The TV show uses a pedagogical discourse, as it proposes to teach young graduates to become reporters and it shows, in its edition, the backstage news (production processes) and the challenges of reporting, showing what, normally, in the television programs of journalism, is left out, such as agenda, direction, and editing. In this sense, it is important to know what is the position occupied by the subject-reporter in this program and if this position is re-symbolized. For this, the corpus consists of 27 discursive sequences and 28 sequences of editions of the program. It was observed that the subject-reporter-apprentice position varies, since this position occupies, throughout the program, a place that canonically does not correspond to the subject-reporter's place. The program is identified with the Literary Journalism format, but it does not hold up as a “doing new journalism”. It is a catching theoretical effect, reproducing Traditional Journalism, mythicized with effects of truth, impartiality, neutrality, and objectivity, which escape, because involvement is not simply a matter of “choice”, but rather a condition for the report production. The sensationalism, the grotesque and the spectacle are characteristics present in Profissão Repórter and they portray the functioning of the television journalistic discourse, which intends, at all costs, from the institutionalized position it occupies, to discourse upon a certain subject as devoid of ideology.